Tinea Capitis Favus-Like Appearance: Problem of Diagnosis - Dwi Ratna Adisty; Linda Astari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Tinea capitis (TC) is an infection of scalp, hair follicles, and the surrounding skin, caused by dermatophyte fungi. Favus, a chronic inflammatory tinea capitis typically seen in Trichophyton schoenleinii infection. Favus is characterized by ‘scutula’. Favus may result in cicatricial alopecia. Purpose: To understand the clinical manifestation and management of tinea capitis. Case: A girl, 8 year-old, 18 kg, with thick crust located at the center of the head since 3 months, became spreading overtime. There were itchy sensation, no fever, no pain. There was history of an itchy red patch on her neck which diminished with topical antifungal. Dermatological examination revealed multiple thick brown-yellow crust sharply marginated, there were erosion and alopecia area beneath the crust. There were no sign of  inflammation, no pustule, no enlargement of cervical and occipital lymphnodes on palpation. Discussion: Wood’s light examination showed no fluorescence and potassium hydroxide (KOH) showed no spores. Result of fungal culture was no colony growth. Patient was given griseofulvin 20 mg/kg body weight/day, wet dressing, and ketoconazole 2% shampoo twice weekly. Good clinical result shown after 10 weeks. Conclusion: Diagnosis of TC established based on history taking, clinical findings, Wood’s light examination, KOH preparation, fungal culture. A negative culture may arise because antifungal treatment had been used prior to collection of the specimen. Griseofulvin still became the drug of choice for tinea capitis even there are new generations of antifungal.